External rhinoplasty in post rhinoscleromatous bulbous Nose (Bangladesh Journal of Otorhinolaryngology, 2013)
A 22-year-old male presented to outpatient department with the complaint of widened nasal tip. He was a known case of rhinoscleroma diagnosed five years ago and had taken treatment for the same for one year. He has been asymptomatic since then. On clinical examination the patient had widening of the dorsum of the nose with a bulbous nasal tip. Anterior rhinoscopy was within normal limits. Rhinoplasty was done and the patient had an improvement in his cosmetic appearance. This is one of unique cases of rhinoplasty on bulbous tip due to rhinoscleroma. DOI: http://dx.doi.org/10.3329/bjo.v19i1.11604 Bangladesh J Otorhinolaryngol 2013; 19(1): 69-72